Final analysis of a 14-year long-term follow-up study of the effectiveness and immunogenicity of the quadrivalent human papillomavirus vaccine in women from four nordic countries. (June 2020) - Kjaer, Susanne K.; Nygård, Mari; Sundström, Karin; Dillner, Joakim; Tryggvadottir, Laufey; Munk, Christian; Berger, Sophie; Enerly, Espen; Hortlund, Maria; Ágústsson, Ágúst Ingi; Bjelkenkrantz, Kaj; Fridrich, Katrin; et al.
Abstract: Background: The quadrivalent human papillomavirus (qHPV) vaccine prevented vaccine HPV type-related infection and disease in young women in the 4-year FUTURE II efficacy study (NCT00092534). We report long-term effectiveness and immunogenicity at the end of 14 years of follow-up after enrollment in FUTURE II. Methods: Young women (16–23 years of age) from Denmark, Iceland, Norway, and Sweden who received three qHPV vaccine doses during the randomized, double-blind, placebo-controlled FUTURE II base study were followed for effectiveness for an additional ≥10 years through national registries. Tissue samples including but not limited to those collected during organized cervical cancer screening programs were obtained from regional biobanks to be adjudicated for histopathology diagnosis and tested for HPV DNA. The observed incidence of HPV16/18-related high-grade cervical dysplasia (primary outcome) was compared with recent historical background incidence rates in an unvaccinated population. Serum was collected at years 9 and 14 to assess antibody responses. Findings: No cases of HPV16/18-related high-grade cervical dysplasia were observed in the per-protocol effectiveness population ( N  = 2121; 24, 099·0 person-years of follow-up) during the entire study. Vaccine effectiveness of 100% (95% CI 94·7–100) was demonstrated for ≥12 years, with a trend toward continued protection through 14 years post-vaccination. Seropositivity rates at study conclusion were >90% (HPV6/11/16) and 52% (HPV18) using competitive Luminex immunoassay, and >90% (all four HPV types) using the more sensitive IgG Luminex immunoassay. Interpretation: Vaccination of young women with qHPV vaccine offers durable protection against HPV16/18-related high-grade cervical dysplasia for ≥12 years, with a trend toward continued protection through 14 years post-vaccination, and induces sustained HPV6/11/16/18 antibody responses for up to 14 years post-vaccination. There was no evidence of waning immunity, suggesting no need for a booster dose during that period. Funding: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA.